Motivasi Orang Tua dalam Menanamkan Nilai-nilai Agama pada Anak Dikalangan Umat Islam dan Umat Khong Hu Chu: Studi Kasus di Kelurahan Pulo Brayan Kota Kecamatan Medan Barat Kota Medan - Harahap, Indriani; Harahap, H. Indra; Utomo, Wahyu Wiji (ANWARUL, 2024)
This research aims to deepen knowledge of parental motivation in instilling religious values in children among Muslims and Confucians, as well as looking for comparisons between the two. This research uses qualitative research, which is field research. This research uses the phenomenological method. This research uses a descriptive approach, the researcher uses interviews and collects some information through documents, books, articles so that this research obtains or collects the results of research conducted both verbal and written information so as to provide clearer information. Based on the findings of this research, religious values in Islam and Confucianism have similarities in goals even though they have different teachings. Religious values in Islam originate and are rooted in belief in the oneness of Allah SWT which is the basis of religion which originates from the Al-Qur'an and Hadith. . The Confucian religion emphasizes noble morals by maintaining good relations between humans in the sky and humans on earth and prioritizing ethics. Instilling religious values in children in Islam can be done by parents always instilling them to worship Allah SWT as the Almighty God, teaching them to do good in social values, praying and always worshiping, and educating children not to lie. Meanwhile, in the Confucian religion, religious values are instilled by educating children to become children with good character, upholding wisdom, loyalty, truth, and instilling human values towards fellow living creatures.